Camera lucida reflections on photography - Barthes, Roland
This is a short book published in 1980 by the French literary theorist and philosopher Roland Barthes. It is simultaneously an inquiry into the nature and essence of photography and a eulogy to Barthes' late mother. The book investigates the effects of photography on the spectator (as distinct from the photographer, and also from the object photographed, which Barthes calls the "spectrum").